FILSAFAT (SISTEM) PEMASYARAKATAN - Iqrak Sulhin (Jurnal Kriminologi Indonesia, 2011)
Part of this article were input material for academic paper in renewing the Indonesian Correctional Law. This efford was conducted in 2009. The main idea of the article is stressing social reintegration as the philosophy of Indonesian corrections (Pemasyarakatan). As a philosophy, Pemasyarakatan first established in 1963-1964 period. The idea of social reintegration in Pemasyarakatan, which is influenced by Bentham and Mills utilitarianism, is not fully mean as a theory for offender treatment in prisons. In practice, the idea of community based correction is compatible with social reintegration. In order to renew the correctional law, some clause in correctional administration are important. In order to achieve the main purpose of social reintegration, whether institutionalized in prison or community based, Pemasyarakatan need appropriate fascilitative support, as well as human resource. The future law need to state the correctional administration explicitly.